A Critique on the Book Philosophy of Social Sciences - Mohammad Shojaeian; Mohammad Reza Taheri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Philosophy of Social Sciences by Michael Root mainly supports a perfectionist approach to the social sciences. In the sense that he believes that social scientists should try to present a conception of the good that is common among research actors. Feminist approaches to the social sciences are examples of this approach. The book also explains the doctrine of neutrality in various areas of social research, which Root believes is the result of the dominance of a liberal approach, and is then rejected. Emphasis on perfectionism in social research and attention to various areas of social sciences is one of the highlights of the book. Failure to provide an explanation of the meaning of the philosophy of social sciences, disregard for developments in contemporary liberalism, in particular, the development of a perfectionist approach to the theory of liberalism and the emphasis on the appropriateness of the idea of neutrality for the state are among the main shortcomings of the book. The existence of a state with valuable moral neutrality challenges the results of perfectionist social research. The issue of objectivity and relativity also needed to be considered, especially for a book that defends the perfectionist approach to the social sciences.